Refined balloon pulmonary angioplasty for inoperable chronic thromboembolic pulmonary hypertension: a prospective multicenter registry. (4th February 2022) - Zhou, Y-P; Wei, Y-P; Yang, Y-J; Peng, F-H; Wu, B-X; Hong, C; Tong, Q; Cui, X-P; Zhang, G-C; Cao, Y-S; Wang, D-L; Xu, X-Q; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): the National Key Research and Development Program of China Background Chronic thromboembolic pulmonary hypertension (CTEPH) is a life-threatening disease with a poor prognosis if left untreated. Pulmonary endarterectomy is the standard treatment for CTEPH, but around 40% of CTEPH patients are non-eligible for surgery. Purpose To investigate the efficacy and safety of refined balloon pulmonary angioplasty (BPA) for inoperable CTEPH in a prospective multicenter registry from China. Methods We conducted a prospective multicenter cohort study using the data from National Rare Disease Registry System of China. Total 140 consecutive patients with inoperable CTEPH who completed BPA between Jan 2016 and Dec 2020 were enrolled. The key efficacy outcomes were changes from baseline to re-evaluation in mean pulmonary arterial pressure, pulmonary vascular resistance, and six-minute walking distance. The safety outcomes were procedure-related complications. The survival outcome was all-cause mortality. Results Among the 140 patients who completed BPA, the mean age at diagnosis was 58 ± 14 years and 60.0% were female. At re-evaluation, the least-squares mean change from baseline was -18.3 mm Hg (95% confidence interval [CI], -19.9 to -16.6, P < 0.001) in mean pulmonary arterial pressure, -5.3 Wood U (95% CI, -5.9 to -4.6, P < 0.001) in pulmonary vascular resistance, and 87 meters (95% CI, 74 to 101, P < 0.001) in six-minute walking distance. BPA procedure-related complications occurred in 109 of 650 BPA sessions (16.8%), but severe complications requiring noninvasive positive pressure ventilation only occurred in 4 (0.6%) BPA sessions. During a mean follow-up time of 32 ± 14 months, 4 patients died, including 2 peri-procedural deaths, contributing to the survival rates of 97.8% (95% CI, 93.4 to 99.3) at 1 year and 96.9% (95% CI, 91.9 to 98.8) at 3 and 5 years. Conclusion Refined BPA appears to be an effective therapeutic option for inoperable CTEPH patients with acceptable safety profiles.